hsa-miR-33-5p as a Therapeutic Target Promotes Apoptosis of Breast Cancer Cells via Selenoprotein T - Zhuang, Wei; Liu, Jianhui; Li, Wenjin (Frontiers in Medicine, 2021)
Objective: Increasing evidence suggests that microRNA (miRNA) participates in regulating tumor cell apoptosis. We aimed to observe the effect of hsa-miR-33-5p on the apoptosis of breast cancer cells and to explore its regulatory relationship with selenoprotein T (SelT). Methods: RT-qPCR was used to examine the expression of hsa-miR-33-5p and SelT both in breast cancer tissues and cells. MCF-7 and MDA-MB-231 cells were transfected with hsa-miR-33-5p mimics or si-SelT. Then, a flow cytometry assay was carried out to examine the apoptosis of cells. Furthermore, SelT and apoptosis-related proteins including caspase-3, caspase-8, caspase-9, Bax, and Bcl-2 were detected via RT-qPCR and western blot. A luciferase reporter assay was utilized for assessing whether SelT was targeted by hsa-miR-33-5p. Results: Downregulated hsa-miR-33-5p was found both in breast cancer tissues and cells. After its overexpression, MCF-7 cell apoptosis was significantly promoted. Furthermore, our data showed that miR-33-5p elevated apoptosis-related protein expression in MCF-7 cells. Contrary to hsa-miR-33-5p, SelT was upregulated both in breast cancer tissues and cells. SelT expression was significantly inhibited by hsa-miR-33-5p overexpression. The luciferase reporter assay confirmed that SelT was a direct target of hsa-miR-33-5p. SelT overexpression could ameliorate the increase in apoptosis induced by hsa-miR-33-5p mimics. Conclusion: Our findings revealed that hsa-miR-33-5p, as a potential therapeutic target, could accelerate breast cancer cell apoptosis.